Relationship between COVID-19 and use of Chlorine Dioxide Gas-Releasing Agents in Elementary Schools (Global Journal of Medical Research, 2023)
Chlorine dioxide has an inactivating effect on various types of viruses in vitro including severe acute respiratory syndrome coronavirus 2 Therefore chlorine dioxide gas can be used as a new preventive measure against coronavirus disease 19 COVID-19 However no studies have been conducted to investigate the relationship between the incidence of COVID-19 and chlorine dioxide We retrospectively studied the occurrence of COVID-19 in 164 public elementary schools under the jurisdiction of boards of education located in urban areas in Japan provided with chlorine dioxide gas-releasing agents or not from January to March 2022 The odds of developing COVID-19 were lower odds ratio 0 934 95 confidence interval 0 895 0 975 in schools provided with chlorine dioxide gas-releasing agents than in schools without them This suggested a relationship between the use of chlorine dioxide-releasing agents and the incidence of COVID-19 Further studies are needed to prove a causal relationship between them
Keywords: chlorine dioxide; COVID-19; infection prevention; elementary school; viral infectivity